Hydrothermally grown α-MnO2 nanorods as highly efficient low cost counter-electrode material for dye-sensitized solar cells and electrochemical sensing applications. (20th October 2017) - Ahmad, Khursheed; Mohammad, Akbar; Mobin, Shaikh M.
Highlights: Hydrothermally grown α -MnO2 nanorods. α -MnO2 nanorods exhibit high surface area. α -MnO2 nanorods employed as counter electrode for DSSC and as modified GCE for electrochemical sensor for p -NT, DNT and TNP. Hydrothermally grown α -MnO2 nanorods. α -MnO2 nanorods exhibit high surface area. α -MnO2 nanorods employed as counter electrode for DSSC and as modified GCE for electrochemical sensor for p -NT, DNT and TNP. Abstract: Multipurpose α -MnO2 nanorods were synthesized by facile hydrothermal method. The synthesized α -MnO2 nanorods were characterized by PXRD, UV- vis, SEM, EDX, TEM and SAED pattern to confirm their purity and morphology. These α -MnO2 nanorods were employed as a low cost counter electrode in dye sensitized solar cell (DSSC) and sensor for the detection of nitroaromatic compounds. DSSC device using α -MnO2 nanorods as counter electrode exhibited excellent power conversion efficiency (PCE) of 4.1% with 0.75 V (Voc) and 0.38 (FF). Furthermore, active surface area of the glassy carbon electrode (GCE) was modified by α -MnO2 nanorods (GCE/ α -MnO2 ) which showed a rapid sensitivity towards p -nitrotoluene ( p -NT), 2, 4-dinitrotoluene (DNT) and 2, 4, 6-trinitrophenol (TNP) with distinct cathodic peaks. TheGCE/ α -MnO2 exhibited the limit of detection (LOD) of 144 nM, 133 nM, 100 nM and a high sensitivity of 17.6 μAμM −1 cm −2, 22.6 μAμM −1 cm −2, 54.82 μAμM −1 cm −2 for p -NT, DNT and TNP, respectively.